Kompetesi Guru dalam Pelaksanaan Evaluasi di SD Sudimara 12 Ciledug Kota Tangerang - Ina Magdalena; Intan Nurhidayati; Annisa Wiji Astuti; Wening Pranidana (Jurnal Halaqah, 2020)
In this article, the aim is to examine in-depth about describing competency in describing competencies. Teacher in preparing learning plans, implementing learning, and evaluating learning in SD Sudimara 12 Ciledug, Tangerang. Types of qualitative research conducted at SD Sudimara 12 Ciledug. Data sources were obtained from one of the teachers and one of the students' interviews. Data analysis in accordance with the objectives of this study is 1). Teachers of SD N 12 Ciledug already have good competence in the learning planning, 2). Teachers of SD N 12 Ciledug already have good competence in the implementation of learning, 3). Teachers of SD N 12 Ciledug already have competency good in carrying out learning evaluations so that learning outcomes achieved at this elementary school also increases.